Research Progress on Recycling of Soy Whey Wastewater - Yiwen SUN; Yating ZOU; Xinyue MA; Miaomiao LIU; Rui LI (Shipin gongye ke-ji, 2022)
Soy whey wastewater(SWW) is produced in the production processes of tofu and soybean protein isolates. It has a large discharged volume and contains rich organic compounds such as whey soy proteins, oligosaccharides and soy isoflavones. At present, SWW is discharged into sewage plants and then treated via biochemical methods by most factories. This results in an increase in the production costs of tofu and soybean protein isolate and a large loss of the organics compounds. Therefore, the recycling of SWW has become a burning problem. On this ground, the studies on the recycling of SWW in recent years were reviewed from two perspectives: recovery of active compounds from SWW and biotransformation of SWW. The advantages and disadvantages of the two perspectives were also described. The results showed that most of the methods for recycling SWW were limited in a lab-scale. Only the recovery of whey soy proteins as animal feeds and biotransformation of SWW into biogas were operated in the industrial scale. On this basis, three future research directions were proposed for promoting the recycling of SWW: reducing the separation costs and increasing the use values of active compounds in SWW, increasing the transformation efficiency and rate of SWW and added values of corresponding products and evaluating the economic benefits of recycling methods to determine the feasibility of their industrialization.